Flora and vegetation of cryoturbed soils and associated habitats in the Cordillera Blanca, Ancash, Peru - Cano, Asunción (2010)
Since 2006 to 2008, floristic and vegetational studies on cryoturbed soils and its associated habitats were carried out in four sites above 4500 m, at Cordillera Blanca (Ancash, Peru). Botanical collections and intersection-line transects were made. The space (in cm) occupied by each species were measurement. A total of 136 species, in 65 genera and 26 families, were recorded. Magnoliopsida (Dicots) were the most diverse (97 spp.), followed by the Liliopsida (Monocots) (36 spp.). The highest species richness was found in the Asteraceae and Poaceae families (40,63%). The most diverse genera was Senecio (18) and Calamagrostis (12 ). We registered 76 species (54,82%) in cryoturbed soils and associates habitats, while 60 species (44,11%) were recorded for the adjacent vegetation. From the total, 95,56% of the species were perennials herbs. Four types of plants comunities were characterized: a) community of cryoturbed soil proper, b) community of cryoturbed soil associated with grassland, c) community of cryoturbed soil associated with dry rocky areas, and d) community of cryoturbed soil associated with humid rocky areas. Species associated to each community are given.